Promotion of Liver Regeneration/Repair by Farnesoid X Receptor in Both Liver and Intestine - Zhang, Lisheng (2012)
FXR is a member of the nuclear receptor superfamily and is the primary bile acid receptor. We previously showed that FXR was required for the promotion of liver regeneration/repair after physical resection or liver injury. However, the mechanism by which FXR promotes liver regeneration/repair is still unclear. Here we showed that both hepatic-FXR and intestine-FXR contributed to promoting liver regeneration/repair after either 70% partial hepatectomy or CCl(4)-induced liver injury. Hepatic FXR, but not intestine FXR, is required for the induction of Foxm1b gene expression in liver during liver regeneration/repair. In contrast, intestine FXR is activated to induce FGF15 expression in intestine after liver damage. Ectopic expression of FGF15 was able to rescue the defective liver regeneration/repair in intestine-specific FXR null mice. CONCLUSION: These results demonstrate that, in addition to the cell-autonomous effect of hepatic FXR, the endocrine FGF15 pathway activated by FXR in intestine also participates in the promotion of liver regeneration/repair.